Bio-Inspired Learning and Adaptation for Optimization and Control of Complex Systems - Na, Jing; Yang, Zhile; Kamal, Shyam; Hu, Liang; Wang, Wenbo; Zhou, Yimin (My University, 2019)
No abstract available
Keywords: Bio-Inspired Learning; Adaptation for Optimization; Control of Complex Systems